Industrial frying trials with high oleic sunflower oil - J. R.K. Niemelä; I. Wester; R. M. Lahtinen (Grasas y Aceites)
High oleic sunflower oil has been developed for some special purposes where a good oxidation stability is needed and a healthy fatty acid profile is preferred. The oil is especially suitable for deep fat frying. These industrial frying trials with high oleic sunflower oil were part of the AIR-project CT 920687 "Utilisation of Sunflower Oils in Industrial Frying Operations". High oleic sunflower oil (HOSO) was tested against the traditional oils and fats in two industrial deep fat frying applications, namely crisps and prefried frozen french fries. The frying trials took place in Raisio Groups factories in Pyhanta and Vihanti, Finland in 1993 and 1994. According to the trials, high oleic sunflower oil is very suitable for deep fat frying. Problems occurred when a hard fat was substituted for a liquid oil in the preparation of prefrozen French Fries. These problems could be partly overcome by adjustments in the processing line.